2020
DOI: 10.1002/glia.23954
|View full text |Cite
|
Sign up to set email alerts
|

Regionally diverse astrocyte subtypes and their heterogeneous response to EAE

Abstract: Astrocytes fulfil many functions in the central nervous system (CNS), including contribution to the blood brain barrier, synapse formation, and trophic support. In addition, they can mount an inflammatory response and are heterogeneous in morphology and function. To extensively characterize astrocyte subtypes, we FACS‐isolated and gene expression profiled distinct astrocyte subtypes from three central nervous system regions; forebrain, hindbrain and spinal cord. Astrocyte subpopulations were separated based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 61 publications
(131 reference statements)
5
34
0
Order By: Relevance
“…The expression of BSG in endothelial cells has been found to be positively correlated with age in humans, which may explain the increased risk of cardiovascular disease with advancing age [19]. Atp1b2 was found to be associated with changes in the microenvironment within the brain, and we hypothesize that the expression of fibroblasts may affect the microenvironment within the brain [20,21]. The main marker genes for oligodendrocytes in the present study were Mbp and Cldn11.…”
Section: Discussionsupporting
confidence: 48%
“…The expression of BSG in endothelial cells has been found to be positively correlated with age in humans, which may explain the increased risk of cardiovascular disease with advancing age [19]. Atp1b2 was found to be associated with changes in the microenvironment within the brain, and we hypothesize that the expression of fibroblasts may affect the microenvironment within the brain [20,21]. The main marker genes for oligodendrocytes in the present study were Mbp and Cldn11.…”
Section: Discussionsupporting
confidence: 48%
“…A widely discussed hypothesis suggests that functional properties of regional astrocytes are mainly determined by the distinct neuronal environments, implying an instructive, and neuronal activity dependent mechanism. However, recent bulk and single cell RNA-Seq data indicate that the molecular properties of astrocytes strongly follow region-and layer-specific cues (Batiuk et al, 2020;Bayraktar et al, 2020;Boisvert et al, 2018;Borggrewe et al, 2020;Chai et al, 2017;Itoh et al, 2018;Lin et al, 2017;Morel et al, 2017;Zeisel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the past decade the functional diversity of astrocytes in distinct brain regions became evident (reviewed by Murai, 2017 andClarke, Taha, Tyzack, &Patani, 2021). It was demonstrated that gene expression changed gradually along the dorsoventral as well as the rostrocaudal axis of the brain (Borggrewe et al, 2020;Morel et al, 2017). Moreover, striatal and hippocampal astrocytes have specialized properties like altered morphology, electrophysiology, and Ca 2+ -signaling within neural circuits (Chai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the observation that statin-mediated inhibition of cholesterol synthesis blocks remyelination (Miron et al, 2009). However, astrocytes, which provide cholesterol in the healthy brain, fail as a local cholesterol source in myelin disease as they strongly downregulate its synthesis both in mouse models (Berghoff et al, 2021;Borggrewe et al, 2021;Itoh et al, 2018) and MS lesions (this study). We hypothesize that chronic myelin disease depletes neuronal and oligodendroglial cholesterol levels, which triggers cell-autonomous cholesterol synthesis by feedback regulation.…”
Section: Disparate Repair Processes During Acute and Chronic Myelin Diseasementioning
confidence: 53%